Comparing laboratory and industrial yeast platforms for the direct conversion of cellobiose into ethanol under simulated industrial conditions. Issue 2 (18th February 2019) - Cagnin, Lorenzo; Favaro, Lorenzo; Gronchi, Nicoletta; Rose, Shaunita Hellouise; Basaglia, Marina; van Zyl, Willem Heber; Casella, Sergio
ABSTRACT: An engineered yeast producing all the cellulases needed for cellulose saccharification could produce ethanol from lignocellulose at a lower cost. This study aimed to express fungal β-glucosidases in Saccharomyces cerevisiae to convert cellobiose into ethanol. Furthermore, two engineering platforms (laboratory vs industrial strain) have been considered towards the successful deployment of the engineered yeast under simulated industrial conditions. The industrial S. cerevisiae M2n strain was engineered through the δ-integration of the β-glucosidase Pccbgl1 of Phanerochaete chrysosporium . The most efficient recombinant, M2n[pBKD2- Pccbgl1 ]-C1, was compared to the laboratory S. cerevisiae Y294[ Pccbgl1 ] strain, expressing Pccbgl1 from episomal plasmids, in terms of cellobiose fermentation in a steam exploded sugarcane bagasse pre-hydrolysate. Saccharomyces cerevisiae Y294[ Pccbgl1 ] was severely hampered by the pre-hydrolysate. The industrial M2n[pBKD2- Pccbgl1 ]-C1 could tolerate high inhibitors-loading in pre-hydrolysate under aerobic conditions. However, in oxygen limited environment, the engineered industrial strain displayed ethanol yield higher than the laboratory Y294[ Pccbgl1 ] only when supplemented with supernatant containing further recombinant β-glucosidase. This study showed that the choice of the host strain is crucial to ensure bioethanol production from lignocellulose. A novel cellobiose-to-ethanol route has been developed and the recombinant industrial yeast could be a promising platform towards the future consolidated bioprocessing of lignocellulose into ethanol. Abstract : This study demonstrates the importance of proper platform selection for bioethanol production by comparing the fermentation profiles of a novel industrial yeast expressing fungal β-glucosidase via chromosomal integration and a known laboratory strain expressing that gene via multicopy episomal plasmid, in presence of increasing concentrations of toxic steam-exploded sugarcane bagasse hydrolysate.